TECHNICAL AND ECONOMIC CHARACTERISTICS OF POSTAL COMMUNICATION TODAY - Nazarova , G.N (Educational Research in Universal Sciences, 2023)
Postal services play a fundamental role in each nation, because of the double impact they generate from a social and economic point of view. Postal services are changing daily in the conditions of Fourth Industrial Revolution. The Fourth Industrial Revolution is a new era in the economic development because of the explosiveness of the technologies development. In this era technology is no longer an enabler, but a business driver. The growth of the internet, mobiles and communication technology has added a different dimension to postal market. The main focus of this article is to discuss the impact of the Fourth Industrial Revolution on postal services. New digital technologies is having a strong influence on the way postal operators are functioning and providing services and will continue to have greater impact in the future. The extend to witch different postal operators are using digital means vary widely and their potential is still far from fully exploited.